COMPARISON ANALYSIS OF ORIGINAL AND COUNTERFEIT COSMETICS BASED ON PERCEIVED QUALITY CASE STUDY ON STUDENTS OF SAM RATULANGI UNIVERSITY - Wuwungan, Ivana .; Pangemanan, Sifrid S.; Tumiwa, Johan R. (Universitas Sam Ratulangi, 2017)
Abstract: Cosmetic is one type of product that often has prestigious prices tied with quality to attract consumers, which (as often is seen with high-priced products) arouses the interests of counterfeiters to copy the originals. Cosmetic can reflect certain life-styles. Cosmetic also can creates different perceived values depending on the consumer. The research aims to find out if there is significant difference in original and counterfeit product based on perceived quality of Sam Ratulangi University. This research conducted by a quantitative method to support the hypothesis. The respondent of this study was using 100 respondents of students in the university. This study was carried out in Samratulangi University. The research adopts comparative research were issued to gather data from the customer to measure their assessment about the original counterfeit cosmetics in the university and their perceived quality. Based on the result of this research, the study found that there are significant diffrence in original and counterfeit. Cosmetics quality perspective of original quality is better than counterfeit quality.Keywords : marketing, counterfeit cosmetics, perceived quality.